TOTAL HIP ENDOPROSTHETICS BY ACETABULAR BONE PLASTY FOR IN DYSPLASTIC COXARTHROSIS USING COMBINED SPINAL-EPIDURAL ANESTHESIA - Shorustamov Muhammad Todjalievich; Nurmetov Sarvar Tadjibayevich; Gaziev Zoir Takhirovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Purpose of the study. The aim of the study was to analyze the results of total hip arthroplasty using bone autoplasty of the acetabular floor in patients with dysplastic coxarthrosis.